Biochar and Nitrogen Effects on Winter Wheat Growth - T. E. Zee; N. O. Nelson; G. Newdigger (Kansas Agricultural Experiment Station Research Reports, 2017)
Biochar, a co-product of thermochemical bioenergy production, may be a valuable soil amendment, but little is known about its potential long-term effects on plant growth and soil fertility. In order to gain more information, this experiment was performed to see if the addition of biochar, in comparison to lime and fertilizer treatments, has the potential to return key nutrients back to the soil or increase crop yield. A field study to investigate the effects of biochar on plant growth was initiated in 2011 near St. John, KS. Treatments included biochar applied at 16.6 ton/a (biochar), lime and annual applications of phosphorus and potassium fertilizer (lime+P&K), and a control. Four rates of nitrogen (N) fertilizer were applied within each treatment (0, 45, 90, and 135 lb N/a). Winter wheat was planted in 2015 and harvested in 2016. The biochar treatment had greater wheat yield and better plant growth than the control but it was similar to the lime+P&K treatment. The greater yields from the biochar and the lime+P&K were likely due to increased soil pH from the lime and biochar. Biochar appears to be an effective method of supplying phosphorus (P), potassium (K), and increasing soil pH, and there was no effect on nitrogen availability.
Keywords: biochar; nitrogen; lime; soil pH; winter wheat